Tuning of whispering gallery modes in a magnetic-fluid-infiltrated silica capillary based on lateral pumping scheme. (9th December 2016) - Li, Yuetao; Zhang, Hao; Liu, Bo; Wu, Jixuan; Song, Binbin; Yan, Donglin; Yang, Chengkun
Abstract: An all-optical tuning method of whispering gallery modes (WGMs) in a silica capillary based on lateral pumping scheme has been proposed and experimentally demonstrated by exploiting the photo-thermal effect of magnetic fluids (MFs) infiltrated into a micro-capillary. The WGMs are coupled from a tapered fiber perpendicular to the silica capillary. Experimental results indicate that the microresonator integrated with MFs shows a Q-factor of 1.2867 × 10 4 and its optical tunability reaches 0.0382 nm/(mW · mm −2 ) under 532 nm laser illumination. Compared with the one infiltrated with pure water, our proposed capillary shows an optical tuning sensitivity increase of about 4270 times. The experimental results on the WGM resonance wavelength sensitivity for the capillaries with different diameters are in accordance with our simulation outcome using radially dependent heat conducting equation. Further experimental studies indicate that the proposed microresonator possesses a good spectral reversibility. Moreover, the dynamic response experiment shows that the rise and fall time of this microresonator is about 231 ms and 255 ms, respectively. The above intriguing features make the proposed WGM resonator a promising candidate for potential applications in optical filtering, microfluidic sensing, and signal processing as well as reconfigurable devices for future all-optical networks.